Endoscopic diagnosis and treatment of calcifying fibrous tumors - Shi, Qiang; Xu, Mei-dong; Chen, Tao; Zhong, Yun-shi; Zhou, Ping-hong; Wu, Hai-fu; Yao, Li-qing (Turkish Journal of Gastroenterology, 2014)
Abstract Background/Aims: The calcifying fibrous tumor (CFT) is classified as a benign fibrous lesion, and it is a rare pathologic entity. We evaluated the feasibility, efficacy and safety of endoscopy treatment for CFT. Materials and Methods: We retrospectively analyzed a total of 4 gastric CFTs that were treated with ESD or EFR at the endoscopic center of Zhongshan Hospital, Fudan University, in Shanghai, between Jan 2007 and Sept 2011. We used endoscopic ultrasound (EUS) to assess whether endoscopy treatment was suitable. Tumor characteristics, complications, the en bloc resection rate, and the local recurrence rate were evaluated. Results: Of the 4 patients, the median age was 55.5 years old. The mean maximum size of the lesions was 1.95±0.67 (range: 1.0-2.5). The EUS features of the lesions included a mass in the muscularis propria of the gastric wall and a heterogeneous hypoechoic (1/4) or homogeneous (3/4) hypoechoic pattern. All of the endoscopic treatments were completed successfully. The en bloc resection rate was 100%. Confirmed diagnoses were made by pathologic results. No local recurrence or complications were observed during the follow-up period (ranging from 15 to 28 months). Conclusion: Endoscopic treatment, especially ESD/EFR, appears to be a feasible and safe procedure for CFT with relatively few complications and low mortality.